Colours of India: Uniting Endocrinologists in Fitness and Friendship - Nagendra, Lakshmi; Bhattacharya, Saptarshi; Kapoor, Nitin; Shaikh, Shehla; Das, Sambit; Mondal, Sunetra; Khare, Jaideep; Kota, Sunil; Mittal, Sachin; Mittal, Rajneesh; Sukumar, Suja; Selvan, Chitra; et al. (Indian journal of endocrinology and metabolism, 2024)
Abstract Colours of India is an annual cultural phenomenon that transcends the boundaries of professional conferences, uniting endocrinologists through the universal language of music and dance. Since its inception in 2016, this vibrant event has brought together teams from across India and other participating countries, showcasing diverse dance forms while fostering friendships, promoting wellness, and celebrating cultural diversity within the medical community.